2021
DOI: 10.1088/1361-6668/ac23ba
|View full text |Cite
|
Sign up to set email alerts
|

New insight into strain and composition of BaZrO3 nanorods in REBCO superconductor

Abstract: We report on strain and composition effects associated with growth of self-assembled BaZrO 3 (BZO) nanorods in REBa 2 Cu 3 O 7−δ (REBCO) superconductors (RE = rare earth = Y and Gd), which have a profound effect on flux pinning and in-field critical current performance. The a-b plane mismatch between BZO and REBCO is never fully coherently accommodated. Instead, the nanorods always assume a size at least one unit cell smaller than the corresponding 'hole' in the REBCO matrix, thus providing deep minima of in-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 91 publications
0
13
0
Order By: Relevance
“…This can be attributed to the fact that the nanorods are not exclusively composed of BZO, but they also contain distorted YBCO or other compounds. The phenomenon also explains the observed difference between the BZO content and the nanorod density. ,, In this case, the observed results would coincide with the experimental observations in the sense that the YBCO + x %BZO can be concluded to grow better on the vicinal substrate.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This can be attributed to the fact that the nanorods are not exclusively composed of BZO, but they also contain distorted YBCO or other compounds. The phenomenon also explains the observed difference between the BZO content and the nanorod density. ,, In this case, the observed results would coincide with the experimental observations in the sense that the YBCO + x %BZO can be concluded to grow better on the vicinal substrate.…”
Section: Resultsmentioning
confidence: 99%
“…The phenomenon also explains the observed difference between the BZO content and the nanorod density. 10,13,51 In this case, the observed results would coincide with the experimental observations in the sense that the YBCO + x%BZO can be concluded to grow better on the vicinal substrate.…”
Section: Improved Flux Pinning Bymentioning
confidence: 99%
“…45,46 The BMO nanorods contain Y in the YBCO+BMO films. 25,47,48 It has been reported that the Y 2 O 3 nanoparticle formation depends on the composition of the Nb site in the double perovskite. 49 The involved RE makes the situation more complicated than the film containing only Y.…”
Section: Resultsmentioning
confidence: 99%
“…In the bulk and the pure film, Y 2 O 3 and/or Y 2 BaCuO 5 precipitate depending on the composition and the kinetic factors. , The BMO nanorods contain Y in the YBCO+BMO films. ,, It has been reported that the Y 2 O 3 nanoparticle formation depends on the composition of the Nb site in the double perovskite . The involved RE makes the situation more complicated than the film containing only Y.…”
Section: Discussionmentioning
confidence: 99%
“…When looking at the volumetric ratio between the YBCO matrix and BZO nanorods in Table , it is obvious that the nanorod density decreased with increasing deposition distance from above 50% at T25 to 32.5% at T45. Because we have earlier demonstrated by XRD that the amount of crystallized BZO is independent of the deposition distance of ≈2% but, on the other hand, the relative Zr ratio measured by EDS is only slightly decreased with increasing deposition distance, being close to the nominal 4% value (Figure ), the difference between the BZO content and nanorod density is more likely related to the composition of the nanorods, where distorted YBCO is also composed in the nanocolumns. …”
Section: Resultsmentioning
confidence: 71%